2008
DOI: 10.1099/mic.0.2007/010470-0
|View full text |Cite
|
Sign up to set email alerts
|

cis- and trans-acting elements involved in regulation of norB (norZ), the gene encoding nitric oxide reductase in Neisseria gonorrhoeae

Abstract: The ability of Neisseria gonorrhoeae to reduce nitric oxide (NO) may have important immunomodulatory effects on the host during infection. Therefore, a comprehensive understanding of the regulatory mechanism of the nitric oxide reductase gene (norB) needs to be elucidated. To accomplish this, we analysed the functional regions of the norB upstream region. The promoter contains an extended "10 motif (TGNTACAAT) that is required for high-level expression. Deletion and substitution analysis of the norB upstream r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 48 publications
2
76
0
Order By: Relevance
“…It is possible that Fur bound to the ompT promoter interacts directly with RNA polymerase, or it may alter the supercoiling or bending of the DNA to promote transcription. It is interesting that the putative Fur box in the ompT promoter is located in a position upstream of the Ϫ10 and Ϫ35 sites similar to that of the Fur box in N. meningitidis norB, a nitric oxide reductase gene that, like ompT, is positively regulated by iron and Fur (7,16). This suggests that Fur bound to sites upstream of the polymerase binding site allows the enhanced transcription of the gene, while Fur sites that overlap the RNA polymerase recognition site mediate the repression of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that Fur bound to the ompT promoter interacts directly with RNA polymerase, or it may alter the supercoiling or bending of the DNA to promote transcription. It is interesting that the putative Fur box in the ompT promoter is located in a position upstream of the Ϫ10 and Ϫ35 sites similar to that of the Fur box in N. meningitidis norB, a nitric oxide reductase gene that, like ompT, is positively regulated by iron and Fur (7,16). This suggests that Fur bound to sites upstream of the polymerase binding site allows the enhanced transcription of the gene, while Fur sites that overlap the RNA polymerase recognition site mediate the repression of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The NsrR protein, which is also predicted to contain an Fe-S center (2), represses the expression of the norB gene, but repression is lifted on exposure to low concentrations of NO (20,41). If the interpretation of the effects of a dnrN mutation on aniA expression is correct, it can be predicted that exposure to NO would result in a rapid increase in norB expression.…”
Section: Resultsmentioning
confidence: 99%
“…these genes (20,28,36,50). These genes include those encoding iron-scavenging receptors and iron-regulated transporters (fbpA, hemO, tbpA, tbpB, fetB, and tonB) and genes encoding enzymes which require iron as a cofactor such as sodB (20,28,36,50).…”
Section: Discussionmentioning
confidence: 99%
“…A separate report has demonstrated that in N. gonorrhoeae Fur can function to activate transcription of the norB gene. In this case, gonococcal Fur was demonstrated to bind to the same site in the promoter region of norB as ArsR, resulting in derepression of transcription in a mechanism similar to that found in E. coli with H-NS (36). Despite these recent studies, more global knowledge of Fur-dependent activation of transcription in N. gonorrhoeae is lacking due to the absence of a defined gonococcal fur mutant.…”
mentioning
confidence: 99%
See 1 more Smart Citation